Epigenetic modifications in solid tumor metastasis in people of African ancestry - Oladipo, Elijah Kolawole; Olufemi, Seun Elijah; Adediran, Daniel Adewole; Adejumo, Isaac Oluseun; Jimah, Esther Moderayo; Oloke, Julius Kola; Udekwu, Chinedum C.; Ogunwobi, Olorunseun O. (Frontiers in Oncology, 2024)
This review focuses on the critical role of epigenetic modifications in solid tumor metastasis, particularly in people of African ancestry. Epigenetic alterations, such as DNA methylation, histone modifications, alterations in non-coding RNAs, and mRNA methylation, significantly influence gene expression, contributing to cancer development and progression. Despite the primary focus on populations of European, American, and Asian descent in most cancer research, this work emphasizes the importance of studying the unique genetic and epigenetic landscapes of African populations for a more inclusive approach in understanding and treating cancer. Insights from this review have the potential to pave the way for the development of effective, tailored treatments, and provide a richer resource for understanding cancer progression and metastasis. Specific focus was placed on the role of DNA methylation, histone modifications, non-coding RNAs, and mRNA methylation in solid tumor metastasis, including how these modifications contribute to the regulation of tumor suppressor genes and oncogenes, influence cellular pathways and signaling, and interact with the immune system. Moreover, this review elaborates on the development of epigenetic-targeted therapeutic strategies and the current advances in this field, highlighting the promising applications of these therapies in improving outcomes for African ancestry populations disproportionately affected by certain types of cancer. Nevertheless, this work acknowledges the challenges that lie ahead, particularly the under-representation of African populations in cancer genomic and epigenomic studies and the technical complications associated with detecting subtle epigenetic modifications. Emphasis is placed on the necessity for more inclusive research practices, the development of more robust and sensitive methods for detecting and interpreting epigenetic changes, and the understanding of the interplay between genetic and epigenetic variations. The review concludes with an optimistic outlook on the future of epigenetic research in People of African ancestry, urging the concerted efforts of researchers, clinicians, funding agencies, and policymakers to extend the benefits of this research to all populations.